Can Oil Prices Volatility Explain Economic Growth? - Al-Harbi, Ahmad; Ahmad, Moid U. (International Journal of Energy Economics and Policy, 2024)
The research focuses on the relationship between oil price volatility and economic activity in the context of a sample of six GCC countries. The study derives the results from an annual data set (1998-2021) and involves correlations, linear regression, curvilinear regression, panel data regression and causality tests to draw conclusions. It was observed that panel data analysis with random effects was best able to explain the positive relationship between oil price volatility and economic activity. Kuwait was observed as an exception country in the study as it demonstrated insignificant relationships and differentiating behavior. The global financial crisis was observed as a significant event on global oil volatility.